PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP RISIKO KEBANGKRUTAN PADA PT. MATAHARI DEPARTMENT STORE TBK - Priatna Kesumah; Valerie Theophanye; Ersa Novell Ramadhanti; Shilmi Fadhilla Syam; Aghniya Sabila Novaghiya; Gunardi Gunardi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
The problem of financial difficulties is a major problem that every company must experience, this also happens to PT. Matahari Department Store Tbk. Research results show that in 2018-2020 from the results of the current ratio analysis showed a decrease by an average of 90%. Meanwhile, the results of the quick ratio showed an increase in 2019, but experienced a significant decrease in 2020 with an average of 50%. Based on the analysis of current ratio and fast ratio shows that the financial performance of PT Matahari Department Store Tbk in terms of current ratio is classified as